Use of Activated Carbons for Treatment of Water Polluted by the Phenolic Substances - BENTURKI, O.S.; ADDOUN, F. (Asian Journal of Chemistry, 2010)
The activated carbons of different structures were prepared from a drift lignocellulosic of an Algerian jujube shells. The used precursors were heated at 475, 650 and 800°C, in presence of an activating chemical agent. The porosity characterization of the activated carbons obtained, was investigated by BET method. Their application to the environment was studied for the treatment of polluted water by the phenol and the p-cresol. The influence of various parameters such as agitation time, phenolics concentrations, pH and temperature was studied. The Langmuir model was used to describe the experimental results. The results show the role, of the activating chemical agent in the porosity development of materials, by increase of their power adsorbent. It was found that more than 90 % of the phenolic products used in water as pollutants were eliminated by activated carbons. The adsorption was maximum in the pH range 6.2-6.8. The negative values of ΔH confirm the exothermic nature of adsorption.